Building Entrepreneurial Human Capital For Regional Development: Psychological Pathways To Youth Entrepreneurial Goal Intention - Khouroh, Umu; Windhyastiti, Irany; Ratnaningsih, Christina Sri; Akbar, Roby Nur (Badan Perencanaan Pembangunan Kota Malang, 2026)
Regional economic development increasingly depends on the capacity of local systems to regenerate entrepreneurs, innovators, and job creators. However, investments in entrepreneurship education do not necessarily translate into durable entrepreneurial career commitment among young people. This study examines the psychological pathways through which perceived behavioral control develops into entrepreneurial goal intention, positioning university students as a prospective source of entrepreneurial human capital for regional development. Integrating the Theory of Planned Behavior and Social Cognitive Theory, the study investigates the mediating roles of entrepreneurial attitude and entrepreneurial self-efficacy. Data were collected from 349 Indonesian undergraduate students who had taken or were taking entrepreneurship-related courses and were analyzed using Partial Least Squares Structural Equation Modeling and Importance–Performance Map Analysis. The findings indicate that perceived behavioral control does not directly translate into entrepreneurial goal intention, but operates through entrepreneurial attitude and entrepreneurial self-efficacy. Entrepreneurial attitude emerges as the most influential psychological mechanism in strengthening long-term entrepreneurial career commitment, while perceived behavioral control represents an important area for intervention. These findings reveal a capability–commitment gap in which young people may perceive themselves as capable of entrepreneurship without necessarily converting that capability into a sustained entrepreneurial career goal. From a regional development perspective, entrepreneurship programs should therefore move beyond competence building and strengthen the desirability, feasibility, confidence, and ecosystem support needed to convert youth entrepreneurial capability into sustained entrepreneurial commitment.